2008
DOI: 10.1186/bcr2210
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of tumor necrosis factor-α resistant human breast cancer cells reveals a MEK5/Erk5-mediated epithelial-mesenchymal transition phenotype

Abstract: Introduction Despite intensive study of the mechanisms of chemotherapeutic drug resistance in human breast cancer, few reports have systematically investigated the mechanisms that underlie resistance to the chemotherapy-sensitizing agent tumor necrosis factor (TNF)-α. Additionally, the relationship between TNF-α resistance mediated by MEK5/Erk5 signaling and epithelial-mesenchymal transition (EMT), a process associated with promotion of invasion, metastasis, and recurrence in breast cancer, has not previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
92
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 58 publications
8
92
0
1
Order By: Relevance
“…EMT is an important biological process of tumor progression. Recent findings suggest that TNF-a induces snail promoter activity and EMT in MCF-7 breast cancer cells, 20 reinforcing the association between inflammation and EMT.…”
Section: Discussionmentioning
confidence: 62%
“…EMT is an important biological process of tumor progression. Recent findings suggest that TNF-a induces snail promoter activity and EMT in MCF-7 breast cancer cells, 20 reinforcing the association between inflammation and EMT.…”
Section: Discussionmentioning
confidence: 62%
“…The present study mainly focused on the anti-apoptotic mechanisms to discuss the drug tolerance mechanism of breast cancer. Zhou et al (2008) confirmed that breast cancer cell line MCF-7-MEK5 with transfected MEK5 has a stable EMT phenotype, the induced effect of MEK5 is unaffected by carriers and cells with TNF-α tolerance are associated with EMT. Our previous studies found that the expression of FASN, which is a key enzyme of synthetic long chain fatty acids, is significantly upregulated in MCF-7-MEK5.…”
Section: Discussionmentioning
confidence: 57%
“…MCF-7-MEK5 cells have TNF-α tolerance (Zhou et al, 2008). TNF-α is a multifunctional cytokine with biological effects that can cause diseases, such as inflammation, killing or inhibition of tumour cells and proliferation and differentiation of tumour cells, which produces a double-edged sword effect.…”
Section: Mechanism Of Fatty Acid Synthase In Drug Tolerance Related Tmentioning
confidence: 99%
See 2 more Smart Citations